Detection of Inflicted Bruises by Alternate Light: Results of a Randomized Controlled Trial. Issue 4 (3rd February 2020) - Scafide, Katherine N.; Sheridan, Daniel J.; Downing, Nancy R.; Hayat, Matthew J.
Abstract: Bruises are often difficult to detect on victims of violence, potentially impacting investigation and prosecution. The purpose of our randomized controlled trial was to measure the effectiveness of an alternate light source (ALS) within visible and long ultraviolet spectrums at improving bruise detection compared to white light over time. We also examined the effects of skin color, age, gender, localized fat, and injury mechanism on bruise detection. Participants included 157 healthy adults with balanced sampling across six skin color categories. Bruises were created under the controlled application of a paintball pellet and dropped weight to one upper and lower arm, respectively. Using a crossover design, both bruises were examined 21 times over 4 weeks. Ten different wavelength (350–535 nm) and filter (yellow, orange, red) combinations were used. Multilevel models were used to analyze 2903 examinations on both upper and lower arms. Results in multivariable models showed after controlling for other covariates 415 and 450 nm using a yellow filter had greater odds of detecting evidence of bruising than white light (Upper Arm: 415 nm: OR = 5.34, 95% CI: 4.35–6.56; 450 nm: OR = 4.08, 95% CI: 3.36–4.96). Under either light source, being female and having more localized fat had increased odds of detecting bruises created by the dropped weight (female: OR = 2.96, 95% CI: 2.37–3.70; fat: OR = 1.21, 95% CI: 1.09–1.34). Our results support ALS as an appropriate tool to enhance concurrent physical assessment of bruises in the presence of known history of injury. Future development and evaluation of clinical practice guidelines for ALS application are needed.